Tourism and national identities - Frew, Elspeth. (Contemporary geographies of leisure, tourism, and mobility., 2011)
"By understanding tourist destinations through the lens of national identity, the tourist may develop a deeper appreciation of the destination. Further, tourism marketers and planners may be better equipped to promote and manage the destination, particularly with regard to expectations of the potential visitor. Tourism and National Identity is the first volume to fully explore the relationship between tourism and national identities and the multiple ways in which cultural tourism, events and celebrations contribute to national identity. It examines core topics critical to understanding this relationship including: tourism branding, stereotyping and national identity; tourism-related representation and experience of national identity; tourism visitation/site/event management; and, the relationship to cultural tourism. The book looks at a range of international tourist sites and events, combines multidisciplinary perspectives and international cases to provide a thorough academic analysis. The interconnecting area of cultural tourism and national identity has been largely overlooked in the academic literature to date. This book gives considerable analysis to the complex relationship between the two domains , and indeed, the multifaceted strategies used to define that relationship.Written by an international team of leading academics, Tourism and National Identities will be of interest to students, researchers and academics in tourism and related disciplines such as events, cultural studies and geography"--